Procedure for analyzing the behavior of the costs to calculate the breakeven point - Hernandez L., Celia (2016)
The breakeven point is a key tool in all-inclusive hotels to determine the number of tourists and revenues should enter the hotel so there from start generating profits.There are difficulties in the classification of costs in hotels semivariable ignoring his behavior, however, to calculate the breakeven point is necessary to separate the fixed and variable part of each of them.In researching the method of least squares is used to separate the fixed and variable costs of mixed and then calculate the actual value of the equilibrium point.It is concluded that the classification of fixed and variable costs proposed by the Ministry of Tourism can accurately determine the equilibrium point, and the application of the least squares method can separate the fixed part and variable costs mixed.